Influence of Swelling on Shear Strength of Expansive Soil and Slope Stability - Lan, Tian; Zhang, Rui; Yang, Biyu; Meng, Xiong (Frontiers in Earth Science, 2022)
Rainfall is the main factor leading to the landslide of expansive soil slope. To deeply understand the instability mechanism of expansive soil slope under rainfall conditions, it is necessary to clarify the strength attenuation mechanism of expansive soil caused by water absorption and swelling. Therefore, the improved constant volume direct shear test was used in this study to compare with the conventional test, focusing on the variation of effective shear strength parameters with dry density (volume), further studying the microscopic mechanism of expansive soil strength attenuation, and combining with numerical calculation to analyze the influence of swelling on slope stability. The results show that the improved direct shear apparatus and method can keep the volume of expansive soil specimens unchanged before and after shear, and obtain the real effective shear strength index of soil. Under the same conditions, the shear strength index of the improved direct shear test is lower than that of the conventional direct shear test. The clay particles will be broken and dispersed when the montmorillonite crystal layer minerals rich in expansive soil absorb water, which is one of the fundamental reasons for the strength difference between expansive soil and ordinary clay. In slope stability analysis, the effect of swelling on the shear strength of slope cannot be ignored and should be considered in engineering design.